Water Concentration in Single‐Crystal (Al,Fe)‐Bearing Bridgmanite Grown From the Hydrous Melt: Implications for Dehydration Melting at the Topmost Lower Mantle - Fu, Suyu; Yang, Jing; Karato, Shun‐ichiro; Vasiliev, Alexander; Presniakov, Mikhail Yu; Gavrilliuk, Alexander G.; Ivanova, Anna G.; Hauri, Erik H.; Okuchi, Takuo; Purevjav, Narangoo; Lin, Jung‐Fu (Geophysical research letters, 2019)
High‐quality single‐crystals of (Al,Fe)‐bearing bridgmanite, Mg0.88 Fe3+0.065Fe2+0.035Al0.14Si0.90O3, of hundreds of micrometer size were synthesized at 24 GPa and 1800 °C in a Kawai‐type apparatus from the starting hydrous melt containing ~6.7 wt% water. Analyses of synthesized bridgmanite using petrographic microscopy, scanning electron microscopy, and transmission electron microscopy show that the crystals are chemically homogeneous and inclusion free in micrometer‐ to nanometer‐spatial resolutions. Nanosecondary ion mass spectrometry (NanoSIMS) analyses on selected platelets show ~1,020(±70) ppm wt water (hydrogen). The high water concentration in the structure of bridgmanite was further confirmed using polarized and unpolarized Fourier‐transform infrared spectroscopy (FTIR) analyses with two pronounced OH‐stretching bands at ~3,230 and ~3,460 cm−1. Our results indicate that lower‐mantle bridgmanite can accommodate relatively high amount of water. Therefore, dehydration melting at the topmost lower mantle by downward flow of transition zone materials would require water content exceeding ~0.1 wt%. Plain Language Summary Water cycle between surface oceans and Earth's deep interior is a key to understanding the evolution and physical/chemical states of the planet. Early studies show that major transition zone minerals, wadsleyite, and ringwoodite, could accommodate abundant water (1–3 wt%), in the form of lattice‐bonded hydrogen atoms, in their crystal structures. However, water solubility in lower‐mantle bridgmanite, the most abundant mineral in the most volumetric layer of the planet, has remained poorly understood. The scientific challenge here was largely due to difficulties in making large‐sized high‐quality single‐crystals of bridgmanite for reliable characterizations of its water concentration. Here we synthesized single‐crystal bridgmanite of a few hundred micrometers in diameter, which are examined to be inclusion and precipitate free and thus can be used for reliable water concentration measurements using NanoSIMS analyses. Unpolarized and polarized FTIR analyses are used to identify characteristic OH‐stretching bands. Our results show that (Al,Fe)‐bearing bridgmanite could contain as high as 1,020(±70) ppm wt water. This high water concentration in bridgmanite has implications for our understanding of how melting can occur deep in the mantle below the transition zone. Key Points High‐quality, inclusion‐free bridgmanite single crystals (Mg0.88Fe3+0.065Fe2+0.035Al0.14Si0.90O3) were synthesized and characterized The crystals contain ~1,020(±70) ppm wt water using NanoSIMS and show pronounced OH‐stretching bands at ~3230 and ~3460 cm‐1 in FTIR spectra Dehydration melting at the topmost lower mantle can occur when water content exceeds ~0.1 wt% solubility limit